Long-distance and dynamic seed dispersal from horseweed (Conyza canadensis). Issue 3 (3rd July 2018) - Liu, Jun; Qi, Meilan; Wang, Junming
ABSTRACT: Seed dispersal has significantly contributed to horseweed invasion in ecosystems. However, there is a lack of research on long-distance (more than 1 km) and dynamic (hourly) seed movement during an entire seed-shedding season and under different atmospheric conditions. To fill this knowledge gap, the Hybrid Single-Particle Lagrangian Integrated Trajectories (HYSPLIT) model, accounting for meteorological factors and biological dynamics (hourly-order seed emission), was validated using experimental data. The validated model was run for different atmospheric conditions (wind speed and updraft-vertical turbulence) to estimate the longest distance (LD, from the source with more than 1 seed ha −1 deposition) and distribution of seed dispersal during one day (8:00 to 18:00). In a weak wind condition (1–4 m s −1 at 10 m height, standard deviation of vertical wind velocity = 0.5–0.6 m s −1 ), LD was about 36.5 km, and 4% of seeds were deposited farther than 5 km. In a strong wind condition (5–7 m s −1, 0.8–1 m s −1 ), LD was 165 km, and 27% were blown farther than 5 km. At the end of the seed-shedding season (44 days), seed dispersal exceeded 186 km; 79% were found within 5 km and 14% were blown farther than 10 km.